PERANCANGAN DAN PEMBUATAN PROGRAM SISTEM INFORMASI GEOGRAFIS PENYEBARAN PRODUK DI INDONESIA DENGAN GOOGLE MAPS - Hendra Hendra; Wasino Wasino; Hadi Sutopo (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Maps used in the manufacture of this application is Google Maps. The methodology used in the manufacture of this application is prototyping methodology. Modeling spatial data used is raster data model. Key words Google Maps, Maps, raster data model